PENERAPAN PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN MOTIVASI BELAJAR KELAS VIII MATA PELAJARAN ILMU PENGETAHUAN SOSIAL DI SMP ISLAM AL-MUHSININ RIMBA MELINTANG KABUPATEN ROKAN HILIR - Johan, Rina Selva; ', Susilawati; ', Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : Cooperative Learning Method Jigsaw Type is a learning strategy bydividing students into groups with heterogeneous characteristics. Members of differentgroups have a responsibility to learn a material the same material and subsequentlyformed an expert group to help each other reviewing resource materials section. studentin the group of experts back to the original group to teach other members about thematerial they have learned. Students are evaluated on an individual basis about thematerial that has been studied after allowing for discussion. The purpose of thisresearch is to increase students' motivation in learning social studies in class VIII SMPIslam Al-Muhsinin Rimba Melintang Kabupaten Rokan Hilir. This research wasconducted at the place SMP Islam Al-Muhsinin Rimba Melintang Kabupaten RokanHilir The sample used is the eighth grade students numbered 30 people. Data wascollected using observation sheet for teachers, students and student motivation. Resultsfrom studies class actions (Classroom Action Research) is known that the activity ofteachers in the first cycle the average value of 58.33% (Good), but on the second cycleincreased to 86.11% (Good). For the students of this research activity In the first cycle66.67% (Good), while on the second cycle increased to 83.33% (Good). averageindicator Student Motivation This research results in Cycle I 58.33% (moderate),whereas in Cycle II 77.50% (High). It can be concluded Application of CooperativeLearning Jigsaw can improve students' motivation in learning social studies class VIIISMP Islam Al-Muhsinin Rimba Melintang Kabupaten Rokan Hilir.Keywords : Jigsaw Method, Motivation to learn